Analisis Pengaruh Reflektor terhadap Distribusi dan Intensitas Cahaya pada Sistem Pencahayaan LED SMD - Yahya Ayasy; Munnik Haryanti (Universitas Dirgantara Marsekal Suryadarma, 2026)
The demand for efficient and energy-saving lighting systems continues to increase due to the growing number of human activities in indoor and outdoor environments. Light Emitting Diode (LED) technology is widely used because of its high energy efficiency and long lifespan. However, the wide beam angle of LEDs often causes a portion of the emitted light to disperse and not be effectively utilized. This study aims to analyze the effect of reflector implementation on improving light intensity and distribution in LED-based lighting systems. This research employed an experimental method by designing a lighting system using Surface Mount Device (SMD) LEDs. Two configurations were tested: LEDs without reflectors and LEDs equipped with reflectors. Light intensity was measured using a lux meter at a fixed measurement distance with two reflector angle variations of 120° and 130°. The data were analyzed comparatively to evaluate the improvement in light intensity and lighting efficiency.The results show that the LED without a reflector produced an average light intensity of 321 lux. The use of a reflector with a 120° angle increased the light intensity to 660 lux (105.61% improvement), while the 130° reflector produced 483 lux (50.47% improvement). These results indicate that reflector implementation can significantly improve light distribution efficiency without increasing power consumption.